Non-destructive diagnosis of a hypogean mill. Issue 1 (1st April 2022) - Carrozzo, A. R.; De Giorgi, L.; Leucci, G.; Longhitano, L.
Abstract: The oil production in the "Terra d'Otranto" (the current provinces of Lecce, Brindisi, and Taranto) has accounted for about four centuries, the primary economic resource in the area. It happened in "places" known as the presses that have a constructive peculiarity, as they derived entirely within the bedrock calcarenite like "Lecce stone", "carparo". They were prevalent on the territory of the three provinces and are present both in urban centres and in the farms. These places, vivid and direct testimony of the rural civilization, are now at the centre of extensive restoration and enhancement work. Given the cultural heritage industry in all respects, the "oil mills" are inserted into the channels of the national roads Olive Oil, and Olive Oil Roads named n° six and n° seven (Adriatic and Ionian Antica Terra d'Otranto). The best solution is conservative reuse, even for the underground presses, as with all industrial archaeological heritage. In this case, new functions mean recovering the fine in its historical identity as a cultural centre to activate it as a place or insert it into a circuit in which the museum is faithfully reconstructed the ancient "art" of unique production processes. Here, we present the work carried out to recover, conserve and enhance the underground oil mill located in the centre of Maglie (LE). Right from the initial design stage, there was a close relationship between designers, researchers-CNR for diagnostics and the responsibility of the City of Maglie. After a detailed knowledge of historical material and construction of the hypogeal phenomenon, both a laser scanner and the non-invasive diagnosis by geophysical surveys were performed.